ESG Reporting Practices in India, UK and USA: An International Comparison - Prof. Dr. Srinivas Subbarao Pasumarti, Sanjay Pareek, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objective of this paper is to do a comparative analysis of ESG / CSR / BRR reporting practices in 30 biggest companies of India, UK and USA. For the study, the countries chosen are all common law countries. In particular, the Indian Companies Act, 2013 has placed responsibility on Indian companies pertaining to CSR practices and their disclosures. The Indian Companies Act, 1956 was originally based on the British Company Law, though it has evolved over the years. On the other hand, in USA, the Model Business Corporation Act is not applicable in all states though stock exchange regulations are applicable for companies listed on those exchanges. This paper follows the methodology of Guo and Yang (2014) who study the sustainability reporting in Dow Jones 30 companies. However, this paper extends the study into an international comparison of sustainability reporting practices of top 30 companies of India, UK and USA. The study extends the literature on international comparison of corporate governance practices and contributes to a better understanding of sustainability reporting practices in these countries, specially among the big companies.